A SCIENTOMETRIC ANALYSIS IN ISLAMIC EQUITY MARKET: WHERE SHALL WE GO? - Firmansyah, Muhamad Ferdy (IJIBE (International Journal of Islamic Business Ethics), 2022)
This study aims to determine the development and development of research trends in the published Islamic equity market and to shape research streams. The data used in this study were 449 scientific articles published in the period 1986-2021. The data sources used are scientific journals indexed on Dimension.ai using the search keyword "Islamic Equity Market". Data processing using R Bibliometric Biblioshiny packages. Research in the field of Islamic equity market is dominated by research based on scientific journals. The results found indicate the development of publications researching the Islamic equity market has increased significantly since 2014. This research provides information on the development of research with the theme of Islamic equity market as well as mapping popular streams in Islamic equity market research.